2012
DOI: 10.1158/1940-6207.capr-11-0320
|View full text |Cite
|
Sign up to set email alerts
|

Risk Modification of Colorectal Adenoma byCYP7A1Polymorphisms and the Role of Bile Acid Metabolism in Carcinogenesis

Abstract: Cholesterol 7α-hydroxylase (CYP7A1), the rate-limiting enzyme in the conversion of cholesterol to bile acids, is a postulated gene modifier of colorectal cancer risk and target for the therapeutic bile acid, ursodeoxycholic acid (UDCA). We investigated associations between CYP7A1 polymorphisms and fecal bile acids, colorectal adenoma (CRA), and UDCA efficacy for CRA prevention. Seven tagging, single-nucleotide polymorphisms (SNPs) in CYP7A1 were measured in 703 (355 UDCA, 348 placebo) participants of a phase I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…UDCA efficacy for sporadic adenoma prevention may be modified by genetic variation in CYP7A1, the rate-limiting cholesterol 7a-hydroxylase enzyme that catalyzes the initial step in hepatic bile acid synthesis. 55 Thompson et al 56 also reported a significant influence of sex on the effects of UDCA in a phase III randomized, doubleblind placebo-controlled trial of low-dose UDCA. Although UD-CA was associated with a 36% risk reduction in developing advanced lesions (CRC, HGD, villous or tubulovillous histology, or large [$1 cm] size) among men, there was a 3-fold increase in the risk of advanced lesions with UDCA use among women, particularly obese women younger than 65 years with high dietary fat intake.…”
Section: Discussionmentioning
confidence: 98%
“…UDCA efficacy for sporadic adenoma prevention may be modified by genetic variation in CYP7A1, the rate-limiting cholesterol 7a-hydroxylase enzyme that catalyzes the initial step in hepatic bile acid synthesis. 55 Thompson et al 56 also reported a significant influence of sex on the effects of UDCA in a phase III randomized, doubleblind placebo-controlled trial of low-dose UDCA. Although UD-CA was associated with a 36% risk reduction in developing advanced lesions (CRC, HGD, villous or tubulovillous histology, or large [$1 cm] size) among men, there was a 3-fold increase in the risk of advanced lesions with UDCA use among women, particularly obese women younger than 65 years with high dietary fat intake.…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of fecal bile acid levels for the UDCA trial was completed in conjunction with the parent clinical trial and has been described in detail elsewhere(6, 13). Briefly, at baseline, study participants provided 72-hour stool samples that were frozen and shipped overnight on dry ice to the University of Arizona Cancer Center(13).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, at baseline, study participants provided 72-hour stool samples that were frozen and shipped overnight on dry ice to the University of Arizona Cancer Center(13). Samples were then homogenized with an equal weight of water for 15 minutes and centrifuged(13). Fecal water was comprised of the aqueous phase after centrifugation and was stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations